ETIOPATHOGENESIS, CLINIC, DIFFERENTIAL DIAGNOSIS AND EFFECTIVENESS OF MODERN TREATMENT METHODS OF CHRONIC HEPATITIS (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, special attention is paid to clarifying the factors causing chronic hepatitis, pathogenesis, specific clinical symptoms, important diagnostic factors in diagnosing the disease, and modern principles of treatment.